Comparison of simulation-based interprofessional education and video-enhanced interprofessional education in improving the learning outcomes of medical and nursing students: A quasi-experimental study. (November 2022) - Wu, Jen-Chieh; Chen, Hui-Wen; Chiu, Yu-Jui; Chen, Yi-Chun; Kang, Yi-No; Hsu, Yi-Ting; O'Donnell, John M.; Kuo, Shu-Yu
Abstract: Background: Use of interprofessional education has greatly expanded and is widely used to foster interprofessional collaborative practice competency in health professionals, especially during medical emergencies. Identifying the interprofessional education delivery mode that can maximize learning outcomes within available resources is crucial for achieving the sustainability of an interprofessional education program. Objectives: To examine the learning outcomes of simulation-based interprofessional education and video-enhanced interactive discussion interprofessional education modules and to analyze the variable costs between these two interprofessional education modules. Design: A prospective quasi-experimental study. Setting: A medical university in Northern Taiwan. Participants: 24 medical students and 48 nursing students enrolled in a 4-week simulation-based interprofessional education or video-enhanced interactive discussion interprofessional education program. Methods: Students' medical task performance, critical medical task performance, team behavior performance, and interprofessional collaboration attitude were examined at the pretest and posttest by using an objective structured checklist and team performance rating scale with a hands-on simulation model and structured questionnaires. The variable costs for simulation-based interprofessional education and video-enhanced interactive discussion interprofessional education were estimated upon the completion of the course. Results: All learning outcomes significantly improved for both the groups from the pretest to posttest. After the intervention, the simulation-based interprofessional education group exhibited significantly higher scores in medical task performance, critical medical task performance and team behavior performance than the video-enhanced interactive discussion interprofessional education group at the posttest. No significant difference was noted in interprofessional collaboration attitude between the groups. Cost analysis revealed that the simulation-based interprofessional education program was approximately two times more expensive in terms of staffing costs and required 1.3 times greater space charges than the video-enhanced interactive discussion interprofessional education program. Conclusion: Both simulation-based interprofessional education and video-enhanced interactive discussion interprofessional education modules effectively improved medical and nursing students' medical task performance, critical medical task performance and team behavior performance. The simulation-based interprofessional education group had more favorable learning outcomes, but the associated costs were higher. Educators should consider both learning outcomes and cost when choosing a design strategy simulation-based interprofessional education vs. video-enhanced interactive discussion interprofessional education for interprofessional education module development. Highlights: Simulation-based IPE and video-enhanced interactive discussion IPE effectively improve students' learning outcomes. Simulation-based IPE had more favorable learning outcomes, but the associated costs were higher. The interprofessional collaborative attitude may vary according to the professional domain and content delivery method. Video-enhanced interactive discussion IPE is less costly due to reductions in staffing time and space requirements.